PENDIDIKAN ISLAM MODERAT DALAM PENCEGAHAN PAHAM RADIKALISME DI TANJUNG JABUNG TIMUR JAMBI - Dwi Rahmana; Ali Ahmad Yenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
Moderate Islamic education is absolutely necessary in religion and the state, especially as an effort to prevent acts of radicalism which are currently increasingly disturbing the nation and state. This research aims to find out and examine the contribution of moderate Islamic education in preventing radicalism. The purpose of this research is to contribute to efforts to prevent radicalism through contributing to moderate Islamic education in Jatimulyo village. Dedang and providing motivation to the community that through moderate Islamic education, acts of terrorism and radicalism will be suppressed at their roots.This research is qualitative research using descriptive methods carried out by the Jatimulyo Village Office. The findings is research show that the contribution of moderate Islamic education implemented in Jatimulyo village is able to become an example of religious harmony and culture. This can be seen from the establishment of Jatimulyo Village which is surrounded by people of different ethnicities and people with different religions, but remains harmonious and well maintained. Moderate Islamic education in preventing radicalism is implemented by coexisting with society, implementing tolerance and mutual respect, prioritizing deliberation in decision making, prioritizing brotherhood, togetherness and trust, not fanaticism towards one ideology and respecting other understandings, not being authoritarian and not forcing things. which is not obligatory, not arrogant and does not consider other people infidels, habits and rules, emulating the attitudes, behavior of the Jatimulyo village elders who initially built Jatimulyo village and respect each other.